Getting the anticoagulation right in the intensive care. Issue 2 (5th September 2014) - Thachil, Jecko; Heap, Laura; Nash, Michael; Hay, Charles
Summary: Thromboprophylaxis and antithrombotic treatment are often required in intensive care patients. The current standard anticoagulant of choice is low molecular weight heparins, which do not usually require monitoring and have a very good safety profile. However monitoring is advised in patients at extremes of body weight and, rarely, low molecular weight heparins cause thrombocytopenia. Alternative anticoagulants can also be problematic in patients at extremes of body weight.